The power of financial behavior in emergency funds: Empirical evidence from a developing country - Nguyen, Thi Anh Nhu (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
Emergency funds are considered a buffer against financial shocks, especially for the informal workforce or individuals living in developing countries with lower-middle income. This research investigates the role of financial literacy in emergency funds. Specifically, financial literacy in this research is approached in three aspects financial knowledge, financial behavior, and financial attitude. Logistic and order logistic regression are applied to analyze the data collected from the Southeast region of Vietnam, a developing country in Asia. The results show that those with better financial behavior are more likely to have emergency funds and their savings are adequate to cover 3-month living expenses or more in comparison with those who have worse financial behavior. Furthermore, while the findings emphasize the importance of financial education and income level in establishing an emergency fund, only income level is a crucial determinant of the size of emergency funds. However, financial knowledge and financial attitude are not found to have a statistically significant impact on saving for emergency funds. These findings provide empirical evidence regarding developing countries with lower middle income to support the literature on personal finance and provide policymakers with suggestions on how to improve individuals’ financial behavior and encourage savings for emergency funds.